Rewind forward [compact disc] - Starr, Ringo; McCartney, Paul; Lukather, Steve; Sugar, Bruce (Ringo Starr ; UMe, 2023)
The latest EP from drumming legend Ringo Starr features four new songs from an all-star cast of collaborators, including Sir Paul McCartney, Joe Walsh, Steve Lukather, Benmont Tench, Matt Bissonette, and Bruce Sugar. With singable melodies, upbeat lyrics, and loads of peace and love, this collection is a must-have for any Ringo fan.